Metallic properties of the Si(111) − 5 × 2 − Au surface from infrared plasmon polaritons and Ab initio theory - Hötzel, Fabian; Seino, Kaori; Huck, Christian; Skibbe, Olaf; Bechstedt, Friedhelm; Pucci, Annemarie (Nano letters, 2015)
The metal-atom chains on the Si(111) − 5 × 2 − Au surface represent an exceedingly interesting system for the understanding of one-dimensional electrical interconnects. While other metal-atom chain structures on silicon suffer from metal-to-insulator transitions, Si(111) − 5 × 2 − Au stays metallic at least down to 20 K as we have proven by the anisotropic absorption from localized plasmon polaritons in the infrared. A quantitative analysis of the infrared plasmonic signal done here for the first time yields valuable band structure information in agreement with the theoretically derived data. The experimental and theoretical results are consistently explained in the framework of the atomic geometry, electronic structure, and IR spectra of the recent Kwon-Kang model.